Plasmodium falciparum multidrug resistance 1 gene polymorphisms associated with outcomes after anti-malarial treatment - Veronika R. Laird; Mateusz M. Plucinski; Meera Venkatesan; Kelsey A. Rondini; Milijaona Randrianarivelojosia; Mauricette N. Andriamananjara; Hawela Moonga; Deus S. Ishengoma; Arlindo Chidimatembue; Pedro Rafael Dimbu; Adicatou-Laï Adeothy; Abdoul Habib Beavogui; et al. (Malaria Journal)
Abstract Background Plasmodium falciparum multidrug resistance transporter 1 (Pfmdr1) gene mutations are associated with altered response to artemisinin-based combination therapy (ACT), particularly the combinations containing the partner drugs lumefantrine and amodiaquine (i.e., artemether-lumefantrine [AL] and artesunate-amodiaquine [ASAQ]). Past studies of Pfmdr1 single nucleotide polymorphisms (SNPs) at codons 86, 184, and 1246 have shown different responses to AL and ASAQ. Methods To determine whether infection with parasites carrying specific Pfmdr1 SNPs leads to increased risk of recurrent parasitaemia (recrudescent or new infection), data from 3,915 samples from 16 therapeutic efficacy studies from 13 African countries between 2013 and 2019 were analysed. Results Patients treated with AL and infected with parasites carrying Pfmdr1 N86 were at greater risk of recurrent infection than those whose parasites carried 86Y. After treatment with ASAQ, individuals infected with parasites that carried Pfmdr1 86Y were more likely to experience a recurrent infection. Conclusions These results support prior studies that suggested: (1) patients given AL and infected with parasites carrying N86 were more likely to experience a recurrent infection; (2) patients given ASAQ and infected with parasites carrying 86Y were more likely to experience a recurrent infection. These findings suggest that ACT and Pfmdr1 genotype may influence outcome after Plasmodium falciparum infection.